Partisipasi Ibu Balita Ke Posyandu Melati di Desa Sungai Bertam, Kabupaten Muaro Jambi Tahun 2020 - Triana, Winda; Razi, Pahrur; Sayuti, Solihin (UI Scholars Hub, 2021)
Introduction. Monthly health services for children under five years at Posyandu include implementing health checks, weighing, monitoring nutrition, giving vitamin A, health consultations and immunizations. At the PIR II Bajubang Puskesmas in the Sungai Bertam Village area, there is a Melati Posyandu with a very low coverage of toddler visits. Every month only 50% of the target number of 70 toddlers (D/S) come to visit. Objective. This study aimed to determine the participation of mothers with children under five years in the Posyandu Melati in Sungai Bertam Village. Methods. This research used a descriptive analytic, the population in this study were all mothers with children under five years at the Posyandu Melati, amounting to 70 people, with a technique using the total sampling Results. 68.6% of respondents participated well in Posyandu, 75.7% of respondents had good knowledge, 57.1% had good attitudes and 51.4% had good motivation. There is a significant relationship between the participation of mothers with children under five in weighing to Posyandu on knowledge (p-value 0.004), attitude (p-value 0.000) and motivation (p-value 0.000). Meanwhile, the role of Cadre does not show a significant relationship to the participation of mothers under five to the Posyandu because it has a p-value of 0.843 Conclusion. There is a significant relationship between knowledge, attitude and motivation with mother's participation in weighing at the Melati Posyandu Sungai Bertam Village, Muaro Jambi Regency in 2020.